Value co-creation of Xiaomi in China - Hsien-Chih Kuo; Pin Luarn; I-Jen Chen (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2018)
Purpose: Since service-dominant logic is a theory with co-creation as its central concept, this study uses service-dominant logic as a basis to analyse the business model and factors of Xiaomi Technology so as to understand the reason that Xiaomi Technology was able to develop diverse products within a short time span. Design/methodology/approach: The present study adopted the case study approach. In that direction, the focus group methodology was used. Finally, the proposed conceptual framework was checked with specialists in Taiwan and China to get the Managerial Implication. Findings: The results of this study can help subsequent businesses understand how to use value cocreation to strengthen business models. Research limitations/implications: A limitation stemming from using case study analysis, this study conducted interviews that enabled Xiaomi-related personnel to answer research questions. Although the respondents came from diverse backgrounds, there are still limitations. Originality/value: Very few studies exist on co-creation in the context of case study research. This study utilizes the concept of co-creation to explore Xiaomi's operation in China. Furthermore, this paper also poses management implications of the findings.
Keywords: C32; E52; E58; 330; Co-creation; Xiaomi; Service Dominant (S-D) Logic; Case Study